Solar dryer technology to process and preserve agricultural products in Nigeria - Yamauchi, Futoshi (CGIAR System Organization, 2024)
The solar dryer is a greenhouse-like structure: a metal or wood frame with plastic foil or acrylic glass that hosts well-ventilated tables or racks where sliced farm produce may be spread in thin layers. Compared to the traditional drying method of spreading sliced produce on the ground under the sun, the solar dryer allows a more enable hygienic, quality-preserving processing of perishable farm produce like fruits and vegetables.